Thriving at work : the role of work-life balance and psychological capital - Esvap, Esin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
The growing dynamism of the change in social, economic, and political conditions, influences work environments and thus, employees’ work-life balance. In order to have a sustainable organizational performance, the need for a workforce constantly developing and feeling vital, namely thriving, is gaining importance. One of the purposes of organizational scholarship is to examine the impact of individual and collective outcomes on overall organizational performance, and for this purpose, it is emphasized that thriving is a critical stimulus to increase employee well-being and provides an understanding of organizational capabilities to achieve long-term adaptability. Therefore, organizational scholarship which focus on the understanding of the positive functioning' components in normal and adverse conditions can be enhanced in conjunction with further examination in thriving at work. The main purpose of this study is to investigate the relationship between thriving at work and work-life balance with the mediator role of psychological capital. For this aim, data were collected from 240 employees from various industries and occupational groups, using a one-phase questionnaire. According to the results of the study, it was evidenced that work-life balance and psychological capital have significant effects on thriving. Moreover, it was also observed that psychological capital has partially mediated the relationship between work-life balance and thriving at work. The results support the significance of questioning the relationship between thriving at work, work- life balance and further individual or organizational variables for future research by considering uncertain and changing working condition.
Keywords: Career development.; Psychological capital.; Thriving at work.